Catalytic role of 16‐s‐16 micelles on condensation reaction of ninhydrin and metal‐dipeptide complex. (22nd November 2018) - Kumar, Dileep; Rub, Malik Abdul
Abstract: Catalytic role of 16‐ s ‐16 (s = spacer) micelles on condensation reaction of ninhydrin and metal‐dipeptide ([Cu (II)‐Gly‐Leu] + ) complex have been studied by varying reactants concentration at various temperatures ranges from 333 K to 353 K. The reaction was monitored at definite time interval with the help of UV‐vis spectrophotometer. For evaluation of critical micelle concentration (cmc) of 16‐ s ‐16 surfactants with and without reactants (ninhydrin and metal‐dipeptide complex), conductometic technique was used throughout the study. During kinetic runs, study confirms the first‐order path in complex and fractional‐order path in ninhydrin. Rate constant ( k ψ ) increased with rise in [16‐ s ‐16] below cmc value, then became almost constant with further increase in concentration (like conventional surfactants). Great enhancement in rate value was noted at higher surfactant concentrations. The rate enhancement below and above cmc values of 16‐ s ‐16 surfactants has been accounted in the light of pseudo‐phase model. Kinetic data were used to calculate several factors including micelle‐substrate binding constants and thermodynamic parameters. Abstract : The study disclosed that the reaction was catalyzed more efficiently in gemini than pure water without employing any harsh experimental conditions. Geminis reduced the challenges of catalytic role efficacies needed for more applied uses. Study provides new route for ninhydrin reaction by enhancing rate as well as sensitivity of method. Effect of [16‐s‐16] gemini surfactants on reaction rate of ninhydrin and [Cu(II)‐Gly‐Leu] + : (■) 16‐6‐16, (●) 16‐5‐16, (▴) 16‐4‐16.